Development and Evaluation of Compact Robot Imitating a Hermit Crab for Inspecting the Outer Surface of Pipes. (1st October 2015) - Imajo, Naoto; Takada, Yogo; Kashinoki, Mikiji
Abstract : Terrestrial hermit crabs which are a type of hermit crabs live on land, whereas typical hermit crabs inhabit the sea. They have an ability of climbing a tree vertically. Their claws allow them to hang on the tree. In this study, an outer-pipe inspection robot was developed. Its locomotion mechanism was developed in imitation of the terrestrial hermit crab's claws. It is equipped with two rimless wheels. Each of the spokes is tipped with a neodymium magnet, which allows the robot to remain attached to even a vertical steel pipe. Moreover, the robot has a mechanism for adjusting the camber angle of the right and left wheels, allowing it to tightly grip pipes with different diameters. Experiments were conducted to check the performance of the robot using steel pipes with different diameters, placed horizontally, vertically, or obliquely. The robot attempted to move a certain distance along a pipe, and its success rate was measured. It was found that the robot could successfully travel along pipes with vertical orientations, although it sometimes fell from oblique or horizontal pipes. The most likely reason for this is identified and discussed. Certain results were obtained in laboratory. Further experiments in actual environment are required.